The relationship between chronic pain and health-related quality of life: the mediating roles of frailty and depression in chronic disease patients - Shi, Yongli; Xu, Mengyuan; Yin, Wenqiang; Li, Ziyuan; Dong, Ping; Zhang, Xianqi; Li, Haoqi; Zhuge, Xianglan; Li, Xiaona; Gao, Min; Ma, Dongping; Sun, Kui; et al. (Frontiers in Public Health, 2025)
IntroductionChronic pain (CP) is a prevalent comorbidity in patients with chronic diseases, yet the relationship between CP and health-related quality of life (HRQoL) remain unclear, particularly through the mediating roles of frailty and depression.MethodsWe conducted a cross-sectional survey in two provinces (eastern and central China) from October 2024 to January 2025, enrolling 3,094 patients with chronic diseases. HRQoL was assessed using the EQ-5D scale, while CP status was determined through structured logic-based questions. Frailty was evaluated using the FRAIL scale, and depressive symptoms were measured with the CES-D10. Spearman’s correlation analysis was performed to assess associations among CP, frailty, depression, and HRQoL. A chain mediation model (PROCESS 4.1, Model 6) was constructed, and mediation effects were tested using a bootstrap approach with 5,000 resamples.ResultsFrailty and depression exhibited significant mediating effects in the relationship between CP and HRQoL. The indirect effects of frailty and depression on HRQoL were −0.0747 (95% CI: −0.0881, −0.0618) and −0.0211 (95% CI: −0.0297, −0.0135). Additionally, a significant chain mediation effect was observed (−0.0192, 95% CI: −0.0242, −0.0145). The indirect effect of frailty and depression accounted for 34.09% of the association between CP and HRQoL (total effect: −0.1150, 95% CI: −0.1305, −0.0999).ConclusionThe study findings demonstrated that frailty and depression serve as significant chain mediators in the relationship between CP and diminished HRQoL. Measures should be taken to reduce the incidence and severity of CP in patients with chronic diseases, improve frailty and depression, and thus improve HRQoL.